Temporal and Stratigraphic Framework for Paleoanthropology Sites Within East-Central Area 130, Koobi Fora, Kenya - Mana, Sara; Hemming, Sidney; Kent, Dennis V.; Lepre, Christopher J. (Frontiers in Earth Science, 2019)
In the Koobi Fora region of the northeast Lake Turkana Basin (Kenya) dozens of archeological sites have been studied for decades in order to understand the behavior of Early Pleistocene hominins. Data collected from these sites have been important for demonstrating the manufacture styles of Oldowan stone-tool users, hominin dietary preferences, and processes of Early Stone Age site formation. A particularly rich locality is collection Area 130. Area 130 is noteworthy for hominin fossils KNM-ER 1805 (Homo) and 1806 (Paranthropus) as well as the FxJj 18 site complex, which represents one of the type localities for the Developed Oldowan of Koobi Fora. However, despite research beginning in the late 1960s, and several revisions to the stratigraphy and dating of the Koobi Fora Formation, few published studies provide a detailed chronostratigraphy for Area 130. The lack of a detailed chronostratigraphy has contributed to conflicting interpretations for the dates of the hominin fossils and archaeological sites. Here we present new geochronologic and paleomagnetic data to develop a chronostratigraphic framework that allows us to directly assess the age of the sediments, fossils, and artifacts from Area 130. Individual pumices from the Orange Tuff marker level and a previously unnamed tuff exposed near the FxJj 18 (referred here as the FxJj 18 tuff) archaeological site complex were collected for high precision single crystal 40Ar/39Ar dating. Concurrently, we collected orientated paleomagnetic samples from stratigraphic levels of the KBS Member in Area 130 and used them to develop a magnetostratigraphic section. Our findings allow us to better constrain the stratigraphy of the analyzed sections and can be used to refine the sequence and chronology of the archaeological and fossils sites from Area 130 and other penecontemporaneous sites within the Lake Turkana Basin. Our data show that the first appearance of the Developed Oldowan for Koobi Fora does not correlate with any obvious evolutionary changes represented by the local hominin hypodigm nor with the arrival of a cognitively advanced hominin. Therefore we speculate that the advent of this more sophisticated type of stone tool was a response to a change in the diet of the genus Homo.